Fish by-product meal in diets for commercial laying hens - Silva, André Ferreira; Cruz, Frank George Guimarães; Rufino, João Paulo Ferreira; Miller, Waldo Mateus Plácido; Flor, Nathália Siqueira; Assante, Rafael Torres (Acta Scientiarum. Animal Sciences, 2017)
This study aimed to evaluate the increasing levels (0, 1, 2, 3 e 4%) of fish by-product meal in diets for laying hens on performance, egg quality and economic analysis. A total of 160 Dekalb White hens with 52-wk old were distributed in a completely randomized design with five treatments and four replicates of eight birds each. The experiment lasted 84 days divided into four periods of 21 days. Estimates of fish by-product meal levels were determined by polynomial regression. Differences (p < 0.05) were detected for all variables of performance, in egg weight, yolk and albumen percentage, yolk and albumen height, feed cost and production cost, in which the inclusion of fish by-product meal in the diets showed better results. It can be concluded that fish by-product meal can be used in diets for hens as alternative feed, with better results in egg production, feed conversion, egg weight, yolk-albumen ratio and a reduction in feed cost and production cost.